Infantile idiopathic intracranial hypertension: case report and review of the literature - Francesco Del Monte; Laura Bucchino; Antonia Versace; Irene Tardivo; Emanuele Castagno; Giovanni Pieri; Giulia Pilloni; Enrico Felici; Antonio Francesco Urbino (BMC, 2022)
Abstract Background Idiopathic intracranial hypertension is an infrequent condition of childhood, and is extremely rare in infants, with only 26 cases described. The etiology is still unknown. Typical clinical manifestations change with age, and symptoms are atypical in infants, thus the diagnosis could be late. This is based on increased opening pressure at lumbar puncture, papilloedema and normal cerebral MRI. The measurement of cerebrospinal fluid opening pressure in infants is an issue because many factors may affect it, and data about normal values are scanty. The mainstay of treatment is acetazolamide, which allows to relieve symptoms and to avoid permanent visual loss if promptly administered. Case presentation We report the case of an 8-month-old infant admitted because of vomit, loss of appetite and irritability; later, also bulging anterior fontanel was observed. Cerebral MRI and cerebrospinal fluid analysis resulted negative and after two lumbar punctures he experienced initial symptom relief. Once the diagnosis of idiopathic intracranial hypertension was made, he received oral acetazolamide, and corticosteroids, with progressive symptom resolution. Conclusions Infantile idiopathic intracranial hypertension is extremely rare, and not well described yet. Bulging anterior fontanel in otherwise healthy infants with normal neuroimaging should be always considered suggestive, but can be a late sign, while irritability and anorexia, especially if associated with vomiting, may represent an early sign. In such cases, lumbar puncture should be always done, hopefully with cerebrospinal fluid opening pressure measurement, which is among coded diagnostic criteria, but whose threshold is controversial in infants. Early diagnosis, timely treatment and strict follow-up help to prevent vision loss or death of affected infants.